2015
DOI: 10.7860/jcdr/2015/11257.5705
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Electroencephalogram (EEG) in Different Stages of Chronic Kidney Disease

Abstract: Aim: To study Electroencephalogram (EEG) in different stages of chronic kidney disease (CKD). Materials and Methods:This observational study was carried out in the Department of Medicine, Jawaharlal Nehru Medical College, Sawangi (Meghe), Wardha conducted over a period of 24 months, spanning from August 2011 to August 2013. Eighty three cases of CKD at different stages were studied. EEG was done in all the subjects and the various EEG dynamics like morphometric waveform patterns, symmetricity, amplitude were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…In addition, patients with none to mild frailty in the current study had significantly lower dialysis adequacy (Kt/V) compared to those with moderate to severe frailty (Table 1 ), rendering the former group susceptible to the unfavorable neurologic sequel brought by uremia. Past reports suggested that patients with CKD tend to have more prominent delta wave activities with worsening renal function due to uremic encephalopathy [ 34 ], resulting in the observed increase in delta power among those with mild frailty in the current study. Finally, depression or anxiety reportedly influences delta power in affected patients [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 48%
“…In addition, patients with none to mild frailty in the current study had significantly lower dialysis adequacy (Kt/V) compared to those with moderate to severe frailty (Table 1 ), rendering the former group susceptible to the unfavorable neurologic sequel brought by uremia. Past reports suggested that patients with CKD tend to have more prominent delta wave activities with worsening renal function due to uremic encephalopathy [ 34 ], resulting in the observed increase in delta power among those with mild frailty in the current study. Finally, depression or anxiety reportedly influences delta power in affected patients [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 48%
“…Six patients (60%) of those who had diffuse slowing ( n = 10) were presented by peripheral polyneuropathy. Gadewar et al ( 32 ) showed that, with progression of CKD stage, frontal sharp wave transients were reported in 71.43% of patients at stage 4 and in 50% of those at stage 5. They found a high theta pattern in both stages.…”
Section: Discussionmentioning
confidence: 99%
“…The first EEG recording machine was introduced by Hans Berger in 1929, who suggested that brain currents changed depending upon the functional status of the brain, such as, sleep, anaesthesia, and epilepsy (Siuly et al, 2016). Currently, EEG is expanding beyond sleep, anaesthesia, and epilepsy, and become increasingly important in the diagnosis and treatment of mental and brain neuro-degenerative diseases and abnormalities (Siuly et al, 2016), and other diseases such as chronic kidney disease (Gadewar, 2015), COVID-19 (Petrescu et al, 2020), etc. Recently, it is also used as a neurofeedback method, by means of which the individual may gain better control over the neurophysiological parameters, by inducing changes in brain functioning and, consequently, behavior (Omejc et al, 2019).…”
Section: Electroencephalography (Eeg)mentioning
confidence: 99%